La recepción del Greco desde las artes contemporáneas (siglos XX y XXI) - Emmanuel Marigno (E-Spania)
This article analyses various aspects of Greco’s painting, with the aim of demonstrating some aspects of the modernity of the work of the Toledo Master. It is first of all an intrinsic approach that is adopted, with the highlighting of various plastic characteristics that tend towards a form of atemporality in Greco’s painting. In a second phase, and through an extrinsic reading, it is necessary to appreciate the various modalities of this permanence of Greco’s painting in contemporary creation (installation, painting, video, etc. of the twentieth and twenty-first centuries).